Investment Instruments in the Islamic Financial System: Strengthening Islamic Fiscal Policy - Indra Indra; Mukhtasar; Abdul Jamal (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2026)
This study discusses the role of investment instruments in the Islamic financial system as a strategic mechanism for strengthening Islamic fiscal policy. Islamic finance emphasizes justice, transparency, and sustainability by avoiding riba, gharar, and maysir, while linking financial activities to the real sector. Using a qualitative descriptive approach, this research analyzes secondary data obtained from academic literature, regulatory documents, and reports from Islamic financial institutions. Content analysis, comparative analysis across countries, and bibliometric mapping are employed to identify conceptual relationships and empirical patterns. The results show that Islamic investment instruments such as sukuk, mudharabah, musyarakah, and productive waqf contribute significantly to Islamic fiscal strengthening by supporting public financing, expanding the fiscal base, and promoting equitable wealth distribution. Sovereign sukuk provide an asset-backed and sharia-compliant alternative for infrastructure and social development financing, while profit-and-loss sharing instruments enhance economic participation and real-sector growth. Productive waqf supports long-term social expenditure without increasing fiscal burdens. However, the effectiveness of these instruments depends on regulatory support, market liquidity, and Islamic financial literacy. Overall, the study concludes that integrating Islamic investment instruments into fiscal policy frameworks can enhance fiscal sustainability and promote inclusive economic development in line with maqasid al-shariah.